Ligand-dependent transcriptional induction of lethal autophagy: A new perspective for cancer treatment. Issue 3 (4th March 2018) - Silvente-Poirot, Sandrine; Segala, Gregory; Poirot, Mathias C.; Poirot, Marc
ABSTRACT: Dendrogenin A (DDA) is a mammalian metabolite that displays anticancer and chemopreventive properties in mice. At the cancer cell level, DDA induces differentiation and death. We investigated herein the nature of DDA cytoxicity in cancer cells. We showed that DDA triggers biochemical and cellular features of macroautophagy/autophagy and that autophagy is cytotoxic. DDA induces both the accumulation of pro-lysosomal sterols and stimulates the expression of regulators of autophagy such as NR4A, LC3 and TFEB through binding to the liver X receptor (LXR), a ligand-dependent transcription factor consisting of 2 isoforms, NR1H2 and NR1H3. These effects are not observed with canonical LXR agonists such as the oxysterol 22(R)-hydroxycholesterol or the synthetic molecules T0901317 and GW3965. DDA effects were measured on melanoma and acute myeloid leukemia cells including patient-derived leukemia cells in vitro and in vivo. Importantly the induction of lethal autophagy kills cells independently of their cytogenetic subgroups and does not differentiate bulk cancer cells from cancer cell progenitors. Together these data show that DDA drives LXR to induce the expression of autophagic genes leading to cancer cells death. This opens up new perspectives for cancer treatment.